Technical framework and empirical analysis of resource and environmental carrying capacity evaluation in karst regions under the constraint of ecological civilization - Yang, Wei; Li, Xiaohua; Yang, Yuchi (Frontiers in Environmental Science, 2024)
Evaluating resource and environmental carrying capacity (RECC) within the framework of ecological civilization is essential for reconciling development with ecological preservation and optimizing land-use patterns. This evaluation through the lens of ecological civilization is crucial for effective resource allocation. This article introduces a technical framework specifically designed for analyzing and evaluating resource and environmental carrying capacity in karst regions, focusing on Anshun City in Guizhou Province as a case study. The framework follows a structured approach, i.e., “problem identification, problem decomposition, and decision-making assessment,” which proves effective for these evaluations. Furthermore, the integrated evaluation index system incorporating resources, environment, and socioeconomic factors under the principles of ecological civilization aligns with contemporary developmental requirements while reflecting the distinctive characteristics of the resources and environment in karst regions. This alignment enhances the specificity and relevance of the evaluation methodology. The application of the obstacle degree model strengthened the utility and depth of the evaluation results. Additionally, Pearson’s correlation analysis clarified the complex interrelationships among various index factors, highlighting the significant role of unique local resources in the carrying capacity of karst regions. Additionally, the article reveals a delay in the socioeconomic development of karst regions, which adversely impacts their carrying capacity. Thus, promoting regional economic growth is crucial for enhancing the overall carrying capacity. In light of these findings, the article proposes practical strategies to enhance resource and environmental carrying capacity. These include establishing technical standards for evaluation, accelerating industrial transfers focused on technological innovation, and enhancing market mechanisms for resource allocation.